JURISDICTIONAL ANALYSIS OF LAND AND BUILDING GRANTS TO UNDERAGE CHILDREN TO REALIZE LEGAL ASSURANCE: RESEARCH STUDY AT THE OFFICE OF THE OFFICER OF THE LAND DEAL MAKER IN BATAM CITY - Muhamad Noor, Fadhilah; Nurkhotijah, Siti; Aminah, Titik; Milanie, Feby (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
Grant is a covenant with which the giver in his life freely and cannot be taken back to hand over something to which the recipient receives the gift. As for the question of how grants to minors and symptoms should be performed and how they will be satisfied if they are given to minors. The purpose of this study is to identify the forms of legal protection, constraints, and mechanism for executing child grants and efforts to achieve their completion. The adoption of grants to minors should be accompanied by either the parents or the guardians. The study was empirical juridical, qualitative analysis. The literature of the theory referred to under section 1682 PCT chapter 37 pp no. 24 1997, on which grants still have to be made in front of PPAT. Studies that grant could be granted to minors on the condition that a parent should have a guardian or representation of a child, the problem that occurs in the granting of a child to a minor is that other families demand the right of the grant where it is performed without the consent of another sibling, the way it is done by a notary notarized deed, and then it is renewed with a firm and clear vow. For legal protection against property from minors, legal care can be made through parental or child custody, whether by law or by law, it may not be used to transfer, transfer or distribute the child's wealth unless it is granted by the court.